Using Interlaboratory Proficiency Data to Guide NIR/MIR Calibrations - Rayment, George E; Hill, Roger; Greaves, A. (Tony) (Communications in Soil Science and Plant Analysis, 2012)
There is growing interest in the use of near-range and/or midrange infrared (IR) diffuse reflectance spectroscopy (NIR and MIR) as nondestructive alternatives to chemical testing of soils. This trend is supported by research on how best to correlate IR spectral data with results obtained by conventional laboratory measurements. While for soils there is growing interest in developing local and national calibrations using “legacy” data, the proven analytical performance of provider laboratories now and earlier, the moisture status of reported results, and the method of soil preparation warrant greater attention. Examples for soil carbon (C) and total soil nitrogen (N) from Australasian interlaboratory proficiency testing across multiple years from 1993 are provided to demonstrate the magnitude of past and present measurement uncertainties, including the effects of method and different concentrations. The evidence is sufficient to require those commissioned to develop NIR and MIR calibrations to subject their prototype calibrations to external peer review by participating in credible, independent interlaboratory proficiency testing programs for ≥12 months, including checks on soil moisture status and possible effects of sample preparation. To rate as credible for most uses, the prototype results should be within the interquartile range for each sample and ideally there should be no outliers and few stragglers. Across the period of assessment (1993–2008), users of Walkley and Black organic C and Kjeldahl digestion for total soil N (Kjeldahl method does not measure total N, but most of the organic N plus an undetermined proportion of nitrate and nitrate present in the sample; quantitative inclusion of both requires a modification of the Kjeldahl procedure) declined as use of furnace technologies for soil C and N increased linearly. There is a strong case to commission two or three well-performing and experienced laboratories to reanalyze samples in “legacy” soil collections prior to finalizing predictive relationships with NIR/MIR spectra for the same samples.